2018
DOI: 10.3389/fmicb.2018.03218
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Oropharyngeal Microbiota in Healthy Piglets and Piglets With Respiratory Disease

Abstract: Porcine respiratory disease (PRD) is responsible for severe economic losses in the swine industry worldwide. Our objective was to characterize the oropharyngeal microbiota of suckling piglets and compare the microbiota of healthy piglets and piglets with PRD. Oropharyngeal swabs were collected from healthy (Healthy_A, n = 6; Healthy_B, n = 4) and diseased (PRD_A, n = 18; PRD_B, n = 5) piglets at 2–3 weeks of age from two swine farms in Guangdong province, China. Total DNA was extracted from each sample and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
39
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 31 publications
7
39
2
Order By: Relevance
“…The identi cation of Acinetobacter, Klebsiella, and Weeksella in our study was consistent with their results, but only Klebsiella and Weeksella were reported as members of the core nasal microbiota. When compared to the study of oropharyngeal microbiota from healthy piglets in China [7], Streptococcus and Lactobacillus were the core microbiota in the oropharynx of these healthy piglets consistent with the studies in the UK and Spain [5]. This agreement showed that the nasal and oropharynx of the piglets shared more common bacterial genera compared to the tracheal isolates of the mature pigs in the present study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The identi cation of Acinetobacter, Klebsiella, and Weeksella in our study was consistent with their results, but only Klebsiella and Weeksella were reported as members of the core nasal microbiota. When compared to the study of oropharyngeal microbiota from healthy piglets in China [7], Streptococcus and Lactobacillus were the core microbiota in the oropharynx of these healthy piglets consistent with the studies in the UK and Spain [5]. This agreement showed that the nasal and oropharynx of the piglets shared more common bacterial genera compared to the tracheal isolates of the mature pigs in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…From 116 isolates, our study identi ed 14 bacterial genera, which included four aerobic (Acidovorax, Acinetobacter, Weeksella, and Wohlfahrtiimonas) and ten facultative anaerobic (Aeromonas, Escherichia, Enterobacter, Hafnia, Klebsiella, Macrococcus, Proteus, Providencia, Shewanella, and Shigella) bacterial genera belonging to seven families (Aeromonadaceae, Comamonadaceae, Enterobacteriaceae, Flavobacteriaceae, Moraxellaceae, Shewanellaceae, and Staphylococcaceae) under three phyla (Proteobacteria, Firmicutes, and Bacteroidetes) from the respiratory tracts of healthy pigs. The isolation of Proteobacteria, Firmicutes, and Bacteroidetes could be due to their abundance in the porcine respiratory tract as previously shown from the metagenomic studies of the nasal, oropharyngeal, and lung microbiota [6][7][8][31][32][33][34][35]. Some of these 14 bacterial genera were reported in similar locations of the porcine respiratory tract [5][6][7][8][31][32][33][34][35][36][37][38][39][40].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Up to now, the genus Actinobacillus has never been referenced as one of the most abundant in weaning piglet intestinal microbiota. Nonetheless, this taxon was identified to be predominant in piglet oropharynx which could explain its high abundance in stomach and small intestine samples of our study [39]. The Lactobacillus genus was already found to be predominant in the fecal microbiota of two weeks old suckling piglets [12].…”
Section: Discussionmentioning
confidence: 84%
“…Correct species identification is important especially when isolates are serologically non-typeable or pathotyped by the method according to Howell et al 2017. In both cases Actinobacillus species which are commensals of the respiratory tract might confound results [21,22]. However, the primers for the species marker identified by Howell et al [12] and originally used in their serotyping and pathotyping PCR erroneously identified six isolates in our collection as G. parasuis which could not be confirmed using primers designed by Oliveira et al 2001 [16] and were indeed closely related to Actinobacillus species by cpn60UT sequencing.…”
Section: Species Identificationmentioning
confidence: 81%